(untitled) (Journal of Engineering, 2012)
This research attempts to trace the most significant development caused by the information revolution, namely "the Communication Technology" which reduced the distances between different urban communities, or within a single one, eliminated the geographical boundaries and the transformed the world into a global village. This led to the emergence of new forms and bodies to those urban communities; perhaps the most important is the fragmentation of the major cities and the emergence of (Satellite Cities) with global links, rather than hinterlands to the local capital cities as in the past. But in spite of the technological tide of communications and its inevitable impacts, it stays, with all its possibilities, a reaction that occurs only in one direction and within the limits of no more than sending and receiving nothing more. This is what Arab cities had seen in the recent stages of their change. Here arises the problem of the emergence of the communication act as a "Dogmatic" because the whole world revolved around the communications network ... Which in turn became the heart of the system of this era. In light of this problem, this research has sought to find the act parallel if not alternative that will fold the " Communication " between its wings, making it, the stage of the process of response and interaction surpassing the limits of sending and receiving. In other words the transition from importing technology to the process of contributing to its production. This only takes place through the investment of the Communications Technology to achieve that which is the highest and noblest, posed in this research by the "Communicativeness" between communities. To achieve this goal it took the building of the theoretical framework, in the light of which we put forward the hypothesis of the research that reads (Communication in its technological dimension and Communicativeness in its social dimension, both, play a role in the formulation of Satellite Cities of the twenty-first century through their essential impact on the physical, social and economic infrastructure development of those cities). The research, then, sought to test the validity of this hypothesis and draw conclusions and recommendations.